Intramolecular addition of diarylmethanols to imines promoted by KOt-Bu/DMF: a new synthetic approach to indole derivatives. Issue 17 (8th April 2016) - Chen, Jia-hua; Chen, Zi-cong; Zhao, Hong; Zhang, Ting; Wang, Wei-juan; Zou, Yong; Zhang, Xue-jing; Yan, Ming
Abstract : KO t -Bu/DMF promoted intramolecular addition of diarylmethanols to imines was developed. Abstract : KO t -Bu/DMF promoted intramolecular addition of diarylmethanols to imines was developed. A series of 2, 3-disubstituted indoles was obtained in good yields. A reaction mechanism of radical cyclization and subsequent dehydration is proposed.